THE EFFECTIVENESS OF THE UKRAINIAN HEALTHCARE SYSTEM IN THE PREVENTION OF CARDIOVASCULAR DISEASES IN CONDITIONS OF MILITARY OPERATIONS: AN ANALYTICAL REVIEW - Zhuk, Kateryna; Smiianov, Vladyslav (Eastern Ukrainian Medical Journal, 2025)
Introduction. The full-scale war in Ukraine has created unprecedented challenges for the healthcare system and significantly worsened the cardiovascular health of the population. The sharp increase in stress levels, the displacement of millions of people, the destruction of medical infrastructure, and limited access to treatment have led to an increase in the burden of cardiovascular diseases (CVD). This study examines the main consequences of the war for the Ukrainian public health system in the context of CVD and identifies areas for its adaptation and recovery. Methods. The work is based on the analysis of national statistical reports, documents of the WHO, the World Bank, the ICRC and the Ministry of Health of Ukraine for 2022–2024. Comparative analysis, content analysis of strategic documents and SWOT analysis were used to identify the strengths and weaknesses of the system, its opportunities and threats in the context of prevention and treatment of CVDs. Results. It was found that the destruction of more than 900 medical institutions, the death and migration of personnel, the lack of medicines and the psychological exhaustion of the population became key factors in the increase in cardiovascular risk. Despite this, the system retained its basic functions thanks to the development of telemedicine, mobile clinics and eHealth platforms, which allowed for to support of the provision of emergency care and monitoring of chronic diseases. SWOT analysis revealed strengths (digitalisation, international support) and main threats (economic instability, emigration of personnel). Discussion. The results obtained indicate that the restoration of the public health system should be based on the principles of sustainability and the integration of CVD prevention into national post-war development strategies. Further strengthening of the primary care, the development of intersectoral partnerships and stable financing are necessary conditions for reducing CVD mortality and increasing the resilience of the system in the conditions of a prolonged crisis.